2015
DOI: 10.1111/aas.12519
|View full text |Cite|
|
Sign up to set email alerts
|

Nefopam as an adjunct to intravenous patient‐controlled analgesia after renal transplantation: a randomised trial

Abstract: In combination with fentanyl PCA, nefopam reduced post-operative fentanyl consumption with superior analgesia after renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In Choi et al with maxillofacial surgery, nefopam did not reduce PONV incidence compared with fentanyl, despite of similar analgesic effect [25]. However, several studies showed that nefopam was effective for moderate to high postoperative pain control [26][27][28][29]. In our result, as is consistent with previous results, using nefopam in IV-PCA showed similar effectiveness to conventional fentanyl-based regimen.…”
Section: Discussionsupporting
confidence: 89%
“…In Choi et al with maxillofacial surgery, nefopam did not reduce PONV incidence compared with fentanyl, despite of similar analgesic effect [25]. However, several studies showed that nefopam was effective for moderate to high postoperative pain control [26][27][28][29]. In our result, as is consistent with previous results, using nefopam in IV-PCA showed similar effectiveness to conventional fentanyl-based regimen.…”
Section: Discussionsupporting
confidence: 89%
“…Nefopam is a common postoperative non-opioid, non-steroidal analgesia. The main mechanism of analgesic action of nefopam is through the inhibition of serotonin, norepinephrine and dopamine reuptake [51,52,53,54,55]. A clinical study conducted by Kim and colleagues have demonstrated that patients who were administrated nefopam 48 hours post renal transplant operation consumed 19% less fentanyl compared to the control group.…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
“…A clinical study conducted by Kim and colleagues have demonstrated that patients who were administrated nefopam 48 hours post renal transplant operation consumed 19% less fentanyl compared to the control group. This study suggests that nefopam as an adjunct to standard analgesia, fentanyl, reduced postoperative fentanyl consumption besides also providing better analgesia [54]. In a novel review by Girard et al [55], they have compiled the studies where nefopam was used in combinations with opioids, paracetamol and non-steroidal anti-inflammatory drugs in both preclinical and clinical setting.…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
“…However, other studies have reported that using nefopam in conjunction with opioids for PCA has opioid sparing effects, which can result in a lower incidence of PONV than when using opioids alone [1639404142]. We may not have observed any benefits of nefopam on incidence of PONV because our study population consisted of patients who underwent orthognathic surgery.…”
Section: Discussionmentioning
confidence: 95%